Stiker sebagai Media Sosialisasi Mitigasi Bencana COVID-19 di Ruang Publik Kota Banda Aceh - Desfandi, Mirza; Abdi, Abdul Wahab; Azis, Daska; Zalmita, Novia; Gadeng, Ahmad Nubli (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article discusses the participation of male and female Islamic boarding school students (santriwan and santriwati) in the Real Work Lecture Program (Kuliah Kerja Nyata or KKN) at Ulumul Qur'an Madrasah Tsanawiyah in Langsa, with a focus on the implementation of innovative training programs. Involving programs such as News Anchor, MC in Arabic, and the Art of Crafting Handmade Bouquet Flowers, this research aims to evaluate the positive impact of KKN activities on the development of practical skills and the reinforcement of character values among the students. A thorough analysis of the effectiveness of each training program is also considered, taking into account the extent to which participation in these activities contributes to improving public speaking skills, mastering the Arabic language, and fostering creativity through the art of crafting handmade bouquets. The results of this research provide a clearer insight into the added value of KKN in the context of madrasah education, opening the door for further discussions on the implementation of relevant training programs in preparing students to face the challenges of the modern world.. .